2019
DOI: 10.1155/2019/6890572
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plant Growth with Hematite Nanoparticle Fertilizer Drop and Determining Nanoparticle Uptake in Plants Using Multimodal Approach

Abstract: There is an emerging scientific interest in the use of nanoparticle fertilizers for enhanced agricultural and bioenergy crop production to meet the growing food and energy demands of the world. The objective of designing the nanoparticle fertilizers is to effectively deliver the required nutrients for the plants without adding large quantities of fertilizer to the environment. However, most reports on nanoparticle fertilizers so far, involved the addition of nanoparticles to the hydroponic system or the soil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 43 publications
0
26
1
Order By: Relevance
“…Zinc is rapidly absorbed by flowers, and affects fruit set and development, as well as carbohydrate metabolism and nutrient uptake. Increase in yield of mango trees due to zinc application may be attributed to its role in flower bud differentiation [26]. Usenik and Stampar [114] reported that Zn plays an important role in auxin synthesis and improves metabolite translocation to the site of bud initiation or to the bud itself.…”
Section: Yield and Fruit Qualitymentioning
confidence: 99%
“…Zinc is rapidly absorbed by flowers, and affects fruit set and development, as well as carbohydrate metabolism and nutrient uptake. Increase in yield of mango trees due to zinc application may be attributed to its role in flower bud differentiation [26]. Usenik and Stampar [114] reported that Zn plays an important role in auxin synthesis and improves metabolite translocation to the site of bud initiation or to the bud itself.…”
Section: Yield and Fruit Qualitymentioning
confidence: 99%
“…Mehmood et al (2018) suggested that the addition of organic matter to soil improved plant nutrient uptake by limiting the heavy metal bioavailable concentration in the soil. Positive effects of Fe 0 -NPs on nutrient uptake by plants were also reported in previous studies (Kim et al 2014, Boutchuen et al 2019. It is still not clear how Fe-NPs alone can increase the macronutrient uptake (e.g., N, P, and K) by plants.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 54%
“…Pariona et al [19] and Yuan et al [45] have also pointed out the similar enhancement of growth traits at low nanoparticles dosage in Zea mayz and Capsicum annuum , respectively. Recent findings by Boutchuen et al [46] and Jeyasubramanian et al [47] have also shed light on HNPs associated augmented growth in four legumes and spinach, respectively. Thus, our results further support the biological impact of HNPs and its possible agricultural applications.…”
Section: Resultsmentioning
confidence: 98%